PENERAPAN TEKNIK KOLASE UNTUK MENINGKATKAN KREATIVITAS PADA KEGIATAN MENGGAMBAR PADA ANAK USIA DINI - Rini Wulansari; Dedah Siti Jubaedah; Ifat Fatimah Zahro (IKIP Siliwangi, 2018)
the application of the technique of collage to enhance creativity in early childhood learning to draw. This event will be based on research by the development of creativity in children is low with the emergence of several indicators that have not been developed. Initial observations showed the development of children's creativity has not been well developed. Rogers (Munandar: 2009:18) source of Creativity is an activity to develop potential in creating an idea or the idea of being more mature in order to express the ability of self. Creativity can improve a person's quality of life because of the creative people who can create new inventions. This research aims to find out (1) Conditions of social development of the students before the application of the technique of Collage (2) the results of the use of the application of the tekonik collage in enhancing creativity in early childhood learning to draw. The subject in this study was the son of Group B who are 5-6.